Team Work Support And Position Promotion On Work Enthusiasm Its Implications In Employee Performance Improvement - Satria, Jaka (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
Good work results are a manifestation of many factors, including morale, work team support, and appreciation. That is, performance is the support of many factors that become the power in the implementation of quality work. Self-tendency to work enthusiastically, supportive co-workers, and positional motivation, make employees have more reasons to perform and maintain it. The purpose of this research is to look at the relationship between various factors (emotional, environmental, and organizational) that affect performance increase. In proving the research phenomenon used a quantitative approach with statistical regression testing as an analytical tool. The research sample is civil servants in the government of Sumbawa district, Indonesia. Overall, the number of respondents to the study was 200 people using a simple random sample technique. In collecting data, the method used is distributing questionnaires. The results of the study show that there is a relationship between performance and enthusiasm, support from work teams, and opportunities for promotion. In the moderation model, it can be seen that the role of morale gives more power to increase performance